The efficacy of nitric oxide in stroke (ENOS) trial – where do we stand in Romania? - Szocs Ildiko; Szatmari Szabolcs; Anamaria Jurcau; Aurel Simion; Edith Sisak; Cheryl Renton; Sharon Ellender; Philip Bath (Romanian Journal of Neurology, 2012)
Introduction. Romania ranks third worldwide for stroke mortality. Although high blood pressure (BP) is a major risk factor for stroke incidence and determinant of outcome, the management of BP in acute stroke remains undefined. The present study assesses patients recruited into the ‘Efficacy of Nitric Oxide in Stroke’ (ENOS) trial from Romania, one of 19 participating countries. Methods. ENOS is an international multicentre prospective randomised controlled trial that is assessing the safety and efficacy of: (i) lowering BP with transdermal glyceryl trinitrate, and (ii) whether pre-stroke antihypertensive therapy should be continued or stopped temporarily, in acute ischaemic stroke or primary intracerebral haemorrhage (PICH). Interventions are given for 7 days and the primary outcome, modified Rankin Scale (mRS), is measured at 90 days. Results. 135 patients were recruited from 3 Romanian sites between March 2009 and August 2011; 56% of these patients were also in the continue-stop arm of the trial. In comparison with the Rest of the World (RoW), Romanian patients were recruited earlier (29 vs. 22 hr), had a higher rate of previous high BP (63 vs. 76%), had less severe stroke at baseline (Scandinavian Stroke Scale, SSS 37 vs. 43/58), were less likely to have a PICH (17 vs. 10%), and had more cases of no visible stroke lesions on baseline CT (27 vs. 49%). Impairment (SSS) at day 7 did not differ. As compared to RoW, the length of stay in hospital was shorter in Romania (14 vs. 9 days); the adjusted death rate at follow-up at 90 days was doubled (odds ratio 1.97, 95% confidence intervals 1.07-3.63) although this was not reflected by a difference in the adjusted rate of death or dependency (mRS>2) at 90 days (OR 1.04, 95% CI 0.66-1.63). Conclusion. ENOS will continue recruiting patients until the summer of 2013. The presented data show that enrolment is feasible in Romania and the trial has been found to be easy to manage and recruit into.